DIFFUSION WEIGHTED IMAGING IN WILSON’S DISEASE - Kalekar , Tushar; Jaipuria, Radhika; Hadi, Ayesha; Kuber, Rajesh; Karanjule, Pooja (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2024)
Background: Wilson’s disease is a disorder affecting metabolism of Copper resulting in its accumulation in various organs and thereby various manifestations. Neurologic involvement in Wilson’s disease is well diagnosed using Magnetic Resonance Imaging (MRI). Diffusion-Weighted Imaging (DWI) and Apparent Diffusion Coefficient (ADC) sequences aid to the diagnosis of Wilson’s disease. Objective: To assess the role of Diffusion-Weighted Imaging (DWI) in Wilson's disease and investigate its application in the clinical course of the disease and to study its demographic distribution. Methods: A prospective observational study on 25 patients diagnosed to have Wilson's disease with or without any neurological manifestations was done performing MRI of brain with Diffusion-weighted imaging (DWI). A follow-up of the patients was performed at end of 6 months eliciting their clinical history. Results: In 25 patients studied, 24% patients showed diffusion restriction, corresponded with a poor prognosis as compared to the other 76% with Wilson's disease. Follow-up study after 6 months on these patients revealed that even after having good adherence with de-coppering therapy, these patients showed progressive neurological deterioration. Most of the patients were between the age group 11-20 years accounting for 44% and majority of the patients were males, accounting for 72%. Conclusion: Diffusion restriction imaging can be effective in determining neurological involvement in Wilson's disease. Patients having diffusion restriction can be considered at high risk for neurological deterioration. It is prudent to obtain diffusion restriction imaging at baseline in all patients diagnosed or suspected to have Wilson's disease.